ANALISIS KEMAMPUAN BERPIKIR KREATIF DALAM IPA FISIKA DI SMPN 1 BUKIT BATU PADA TEMA EFEK RUMAH KACA - Viera Rosiyana Sari; Zulirfan Zulirfan; M. Rahmad M. Rahmad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The ability to think creatively is one of the skills needed for individuals to face the era of the Industrial Revolution. The efforts made by researchers are conducting survey research. This research aims to analyze students' thinking skills and find out the differences in creative thinking abilities in science physics on the theme of the greenhouse effect between male and female junior high school students. This research is a research that uses a survey method. The data obtained from this research is the data given to students from the results of the answers to the instrument of creative thinking ability. The instruments used are arranged based on 4 aspects of creative thinking skills, namely fluency, flexibility, originality, and elaboration. The results showed that the average value obtained from the creative thinking ability instrument in physics science on the theme of the greenhouse effect was quite creative and there was a significant difference between the creative thinking abilities of men and women.Keywords: Creative thinking ability, Science, Greenhouse Effect